2009
DOI: 10.1037/a0014700
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial study of the ABRACADABRA reading intervention program in grade 1.

Abstract: This study reports a randomized controlled trial evaluation of a computer-based balanced literacy intervention, ABRACADABRA (http://grover.concordia.ca/abra/version1/abracadabra.html). Children (N ϭ 144) in Grade 1 were exposed either to computer activities for word analysis, text comprehension, and fluency, alongside shared stories (experimental groups), or to balanced literacy approaches delivered by their classroom teachers (control group). Two computer-based interventions-a phoneme-based synthetic phonics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 81 publications
8
41
2
1
Order By: Relevance
“…The effect size for this comparison was large (η 2 =.14), which is all the more promising given the 'at risk' nature of much of our sample (students in remote communities with low attendance who receive less than ideal literacy instruction). The finding of the largest effects on phonological awareness is consistent with previous studies on ABRACADABRA in Canada (Comaskey et al, 2009;Savage et al, 2009) and may be somewhat explained by the training that emphasised ABRACADABRA's use for phonological awareness instruction.…”
Section: Discussionsupporting
confidence: 81%
“…The effect size for this comparison was large (η 2 =.14), which is all the more promising given the 'at risk' nature of much of our sample (students in remote communities with low attendance who receive less than ideal literacy instruction). The finding of the largest effects on phonological awareness is consistent with previous studies on ABRACADABRA in Canada (Comaskey et al, 2009;Savage et al, 2009) and may be somewhat explained by the training that emphasised ABRACADABRA's use for phonological awareness instruction.…”
Section: Discussionsupporting
confidence: 81%
“…Computers can help teachers diagnose reading difficulties, individualize instruction, engage children's attention with dynamic activities, increase implementation fidelity (including through the use of embedded multimedia support for teachers and students), provide instant and consistent feedback, track children's progress, and provide ongoing reports for tutors and teachers (Klein, Nir-Gal, & Darom, 2000). Savage, Abrami, Hipps, and Deault (2009) have developed and carried out a randomized evaluation of ABRACADABRA-a Web-based, multimedia early literacy tool that promotes skills in alphabetics, fluency, comprehension, and writing. Unlike traditional CAI, ABRACADABRA is used in regular reading classes and is fully integrated with other teaching methods.…”
Section: Research Base For Team Alphiementioning
confidence: 99%
“…Mobile technology makes learning across time and contexts possible (Sharples et al, 2009). Past research has identified barriers and supports to integrating computer technology (e.g., Wood, Mueller, Willoughby, Specht, & DeYoung, 2005) and more recent studies have begun to explore how digital technologies support learning and how these technologies impact on learners within and beyond the classroom context (e.g., Lai et al, 2007;Savage, Abrami, Hipps, & Deault, 2009). Although this new research is beginning to provide answers regarding the impact of technology on learning and instruction, many questions are yet unanswered.…”
Section: Importance Originality Contribution To Knowledge and Relatmentioning
confidence: 99%